In vivo activity and pharmacokinetics of nemorosone on pancreatic cancer xenografts - Wolf, Robert; Hoheisel, Jörg D. (PLOS ONE, 2013)
Pancreatic cancer is one of the leading cancer-related causes of death in the western world with an urgent need for new treatment strategies. Recently, hyperforin and nemorosone have been described as promising anti-cancer lead compounds. While hyperforin has been thoroughly investigated in vitro and in vivo, in vivo data for nemorosone are still missing. Thus, we investigated the growth-inhibitory potential of nemorosone on pancreatic cancer xenografts in NMRI nu/nu mice and determined basic pharmacokinetic parameters. Xenograft tumors were treated with nemorosone and gemcitabine, the current standard of care. Tumor sections were subjected to H&E as well as caspase 3 and Ki-67 staining. Nemorosone plasma kinetics were determined by HPLC and mass spectrometry. Induction of CYP3A4 and other metabolizing enzymes by nemorosone and hyperforin was tested on primary hepatocytes using qRT-PCR. At a dose of 50 mg/kg nemorosone per day, a significant growth-inhibitory effect was observed in pancreatic cancer xenografts. The compound was well tolerated and rapidly absorbed into the bloodstream with a half-life of approximately 30 min. Different metabolites were detected, possibly resembling CYP3A4-independent oxidation products. It is concluded that nemorosone is a potential anti-cancer lead compound with good bioavailability, little side-effects and promising growth-inhibitory effects, thus representing a valuable compound for a combination therapy approach.
Gesehen am 22.07.2021